CSC138: Structured Programming / College of Computing, Informatics and Mathematics - UiTM, College of Computing, Informatics and Mathematics (2023)
This course introduces the students to the techniques of programming using an imperative structured language. It covers single and multi-dimensional arrays, records and file processing concepts. Besides covering the basic syntax and semantics, the course emphasizes on problem solving methodology and modular programming techniques.